Evaluation of MYBPC3 trans-splicing and gene replacement as therapeutic options in human iPSC-Derived cardiomyocytes - Prondzynski, Maksymilian; Müller, Oliver J. (Molecular therapy. Nucleic Acids, 2017)
Gene therapy is a promising option for severe forms of genetic diseases. We previously provided evidence for the feasibility of trans-splicing, exon skipping, and gene replacement in a mouse model of hypertrophic cardiomyopathy (HCM) carrying a mutation in MYBPC3, encoding cardiac myosin-binding protein C (cMyBP-C). Here we used human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) from an HCM patient carrying a heterozygous c.1358-1359insC MYBPC3 mutation and from a healthy donor. HCM hiPSC-CMs exhibited ∼50% lower MYBPC3 mRNA and cMyBP-C protein levels than control, no truncated cMyBP-C, larger cell size, and altered gene expression, thus reproducing human HCM features. We evaluated RNA trans-splicing and gene replacement after transducing hiPSC-CMs with adeno-associated virus. trans-splicing with 5′ or 3′ pre-trans-splicing molecules represented ∼1% of total MYBPC3 transcripts in healthy hiPSC-CMs. In contrast, gene replacement with the full-length MYBPC3 cDNA resulted in ∼2.5-fold higher MYBPC3 mRNA levels in HCM and control hiPSC-CMs. This restored the cMyBP-C level to 81% of the control level, suppressed hypertrophy, and partially restored gene expression to control level in HCM cells. This study provides evidence for (1) the feasibility of trans-splicing, although with low efficiency, and (2) efficient gene replacement in hiPSC-CMs with a MYBPC3 mutation.
Gesehen am 09.04.2018